ADSORPTION OF VOLATILE ORGANIC COMPOUNDS ONTO POROUS CLAY HETEROSTRUCTURES BASED ON SPENT ORGANOBENTONITES - Zhu L.; Tian S.; Shi Y. (My University, 2005)
Model spent cetyltrimethylammonium bromide (CTMAB)-bentonite, and cetyl pyridinium chloride (CPC)-bentonite used for sorbing p-nitrophenol (PNP) from wastewater, as well as virgin CTMAB-bentonite and CPC-bentonite, were employed as the starting materials to prepare porous clay heterostructures (PCHs). The BET surface areas and total pore volumes of the PCHs based on these spent and virgin organobentonites (PNP-CTMAB-PCH, CTMAB-PCH, PNP-CPC-PCH and CPC-PCH) are 661.5 m2/g and 0.25 cm3/g, 690.4 m2/g and 0.27 cm3/g, 506.3 m2/g and 0.30 cm3/g, and 525.4 m2/g and 0.30 cm3/g, respectively. These values approximate those of activated carbon (AC), at 731.4 m2/g and 0.23 cm3/g, and are much larger than those of bentonite and CTMAB-bentonite, at 60.9 m2/g and 0.12 cm3/g, and 3.7 m2/g and 0.0055 m2/g, respectively. The PCHs have slightly higher adsorption capacities for benzene and CCl4 than AC at higher relative pressures despite their comparatively lower benzene and CCl4 adsorption capacity at lower relative pressures. The existence of PNP in organobentonites also enhances the volatile organic compounds (VOCs) adsorption capacity of PCHs at lower adsorbate concentrations, although some adsorption capacity is lost at higher concentrations. The hydrophobicity order of the adsorbents is: CTMAB-bentonite> AC> PCHs> bentonite. The micro- to mesoporous pore sizes, superior VOC adsorption properties, thermal stability to 750°C and hydrophobicity and negligible influences of PNP on PCHs make spent PNP-containing organobentonites ideal starting materials for synthesis of PCHs and especially attractive adsorbents for VOC sorption control. Copyright © 2005, The Clay Minerals Society.
Keywords: ADSORPTION; ORGANOBENTONITE; POROUS CLAY HETEROSTRUCTURES; VOC